Structural mechanics characterization of steel intermeshed connection using nonlinear finite element analysis. (1st July 2021) - Shemshadian, Mohammad E.; Schultz, Arturo E.; Le, Jia-Liang; Laefer, Debra F.; Al-Sabah, Salam; McGetrick, Patrick
Highlights: Advanced cutting techniques could help eliminate welding or bolting in steel connections. Abaqus can accurately simulate the global and local behavior of the intermeshed connection. The intermeshed connection transfers loads through interlocking pieces. The modified design procedure assures a practical margin of overstrength in the connection. In the redesigned specimens, most of the damage occurs in the connecting parts as planned. Abstract: The aim of the present study is to develop insights into the structural performance of a recently developed 'intermeshed' steel connection, which transfers loads mainly through direct contact rather than by welds or bolts. This investigation was conducted through a step-by-step state assessment of the intermeshed connection subjected to multiple scenarios of gravity loading and by use of a nonlinear finite element platform. Implementation of the intermeshed connection would cause a discontinuity in the beam, so this paper addresses concerns regarding the load-transfer mechanisms and failure modes for these connections. The finite element simulations were performed in Abaqus, which is capable of handling material and geometrical nonlinearity, as well as the contact between individual surfaces. In order to verify the accuracy of these simulations, the numerical results were compared with experimental data from four physical tests. Finally, some important factors of influence such as connection segments sizes, lateral constraint, support conditions, and failure modes were also investigated through numerical analysis. The results of finite element analysis on different prototypes of steel intermeshed connection showed that the specimens with this connection provided sufficient ductility and resistance to meet design requirements.